Sentimental readers : the rise, fall, and revival of a disparaged rhetoric - Halpern, Faye (University of Iowa Press, 2013)
How could novels like Uncle Tom's Cabin change the hearts and minds of thousands of mid-nineteenth-century readers, yet make so many modern readers cringe at their over-the-top, tear-filled scenes? Sentimental Readers explains why sentimental rhetoric was so compelling to readers of that earlier era, why its popularity waned in the latter part of the nineteenth century, and why today it is generally characterized as overly emotional and artificial. But author Faye Halpern also does more: she demonstrates that this now despised rhetoric remains relevant to contemporary writing teachers and lite.